Fluid Networks and Hegemonic Powers in the Western Indian Ocean - Walker, I.; Ramos, M. J.; Kaarsholm, P. (2017)
The present volume sets forth to analyse illustrative aspects of the deep-rooted immersion of the populations of the eastern coasts of Africa in the vast network of commercial, cultural and religious interactions that extend to the Middle-East and the Indian subcontinent, as well as the long-time involvement of various exogenous military, administrative and economic powers (Ottoman, Omani, Portuguese, Dutch, British, French and, more recently, European-Americans). The present volume is the product of one of the main activities of this CRG: organizing AEGIS international thematic conferences on African in the Indian Ocean. The second such conference took place in Lisbon, at ISCTE-University Institute of Lisbon, on April 10th April 2015, convened by the Centre of International Studies, and organized by Iain Walker (Max Plank Institute), Manuel João Ramos (CEI-IUL), and Preben Kaarsholm (Roskilde University). The chapters in this book are a selection of reviewed and revised contributions to that conference. The chapters are presented chronologically, from the 16th century to the present day, and are contextually paired (Eastern Africa and Madagascar, the Horn, and South Africa). This is certainly not a comprehensive and final book on the intertwining relationship between African participation in the regional trading and cultural networks of the Indian Ocean and the hegemonic presence of world powers in the area. Its purpose is rather to contribute, with a few meaningful exemplary case-studies, to assert the need for further and more inclusive investigation. It touches upon questions that have been independently addressed by different regional and inter-regional research networks (African studies, Gulf studies, Indian Ocean studies, Southwest Asian studies, etc.). The role of the Indian Ocean in global security, the increasing involvement of India and China in the economies of contemporary African states and the cultural links that bind eastern Africa to the Indian Ocean littoral are both intricate and temporally deep. The editors of this book hope that it may serve as a useful tool to bridge the different social sciences and regional studies areas, and create a clearer awareness of the deep-rooted, and evolving, ties between Africa and the Indian Ocean. This publication is funded with national funds by FCT – Fundação para a Ciência e a Tecnologia (in the framework of the project UID/CPO/03122/2013)